Immune dysregulation in the functional gastrointestinal disorders. (9th November 2015) - Keely, Simon; Walker, Marjorie M.; Marks, Ellen; Talley, Nicholas J.
Abstract: Gastrointestinal conditions may be broadly classified into two: organic and functional disease, with functional disorders accounting for the majority of patients with chronic gastrointestinal symptoms. Functional gastrointestinal disorders (FGIDs) present with no obvious pathology or well‐accepted biochemical mechanism and, as such, treatment strategies are limited and focus on symptoms rather than cure. Irritable bowel syndrome and functional dyspepsia are the most widely recognised FGIDs, and there is a growing body of evidence to suggest an underlying inflammatory phenotype in subsets with these conditions. Here, we discuss the current knowledge of immune involvement in FGIDs and the commonalities between the different manifestations of FGIDs and propose a new hypothesis, potentially defining an underlying immunopathological basis of these conditions.